ANALIYSIS OF THE INFLUENCE OF MARKETING MIX, E-TRUST AND LIFESTYLE ON PURCHASING DECISIONS VIA THE BUKALAPAK APLICATION (CASE STUDY OF MUHAMMADIYAH UNIVERSTY OF JEMBER STUDENTS) - Asih, Muslimin Wahyu; Santoso, Budi; Azhad, Muhammad Naely (Univesitas Muhammadiyah Tangerang, 2024)
This research aims to find and analyze the influence of marketing mix, e-trust and lifestyle on purchasing decisions via the Bukalapak Application among Unmuh Jember Students. From the results of the initial survey data, it was found that Bukalapak users who experienced a decline were not only the general public but also students at the Muhammadiyah University of Jember. This decline was caused by several factors including the influence of the marketing mix, level of trust and suitability. This research involved students who had used the Bukalapak application to make purchases. This research used the Proportionate Stratified Random Sampling method with 100 respondents. From this research, results were obtained which showed that partially marketing mix, e-trust and lifestyle had a positive and significant influence on purchasing decisions via the Bukalapak Application among Muhammadiyah University Jember students.